Systematic review of integrated mental and physical health services for children and young people with eating and functional symptoms - Efthalia Massou; Josefine Magnusson; Naomi J Fulop; Saheli Gandhi; Angus IG Ramsay; Isobel Heyman; Sara O’Curry; Sophie Bennett; Tamsin Ford; Stephen Morris (Health and Social Care Delivery Research)
Background Evidence suggests that by recognising the psychosocial component of illness as equally important to the biological components, care becomes more holistic, and patients can benefit. Providing this type of care requires collaboration among health professionals, rather than working in isolation, to achieve better outcomes. However, there is a lack of evidence about the implementation of integrated health care. This review focuses on children and young people experiencing eating disorders (i.e. disorders related to feeding and eating) or functional symptom disorders (i.e. medically unexplained symptoms). Aims The present review is part of a larger study that will inform the development of a new children’s hospital in England. Both eating disorders and functional symptom disorders are conditions that may be particularly likely to benefit from an integrated approach to health care, and this review aims to investigate what service models have been used to integrate care, what factors influence their implementation, and what effects these integrated models have on access to and outcomes from care. Method We conducted a systematic review of studies based on children and young people with eating disorders or functional symptom disorders, investigating the effectiveness of integrated mental and physical health services versus any other type of services provided in these populations. We searched MEDLINE, EMBASE and PsycInfo® (American Psychological Association, Washington, DC, USA) electronic bibliographic databases in July 2024 without restriction on the date of publication or country of interest. We reviewed only studies written in English. Results We identified 2668 citations which resulted in 1939 papers eligible for title screening. Only one single-site Australian evaluation of an integrated care model from over 20 years ago was included in our review. The study reported significantly higher number of total admissions and total bed-days utilised in the integrated approach. However, the burden of care shifted from psychiatric wards to medical wards and as a result, the cost per admission and the cost per inpatient decreased. Limitations The lack of conceptual consistency about the definition of integrated care may have driven false screening and loss of some evidence. The same limitation applies in terms of the definition of functional symptom disorders. Conclusions The review identified a gap in the evidence base relating to integrated secondary service provision for children and adolescents with eating disorders or functional symptom disorders in comparison with generic services. No similar studies were identified for children and young people with functional symptom disorders. Our findings align with previous evidence and show that despite the existence of studies describing aspects of integrated care, integration of physical and mental health services for children and young people with eating disorders or functional symptom disorders is underexplored and the limited available evidence is of weak quality. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR133613. Plain language summary Children and young people with eating disorders (which involves issues with thoughts about food, eating, weight and shape, as well as eating behaviours) and functional symptom disorders (physical symptoms without clear medical explanation) need specialist health care that includes both physical and mental health services. To address the needs of these children and young people, whose number is growing, more recent trends in care are based on team-based care. This kind of care involves healthcare professionals from various specialties and encourages greater collaboration among them. There are studies that show that children and young people receiving this kind of care – also known as integrated care – might have better outcomes. The aim of this review was to search the relevant literature for studies that explore how this care is implemented and what its impact is on patients with these two conditions. We reviewed existing studies to see how integrated health services (combining mental and physical health care) are being used for these conditions. We specifically looked for studies that compared integrated services to regular, non-integrated services. We found only one study exploring the impact of this kind of care for children and young people with eating disorders. We extracted useful information from this study, and we assessed its quality. That study found that integrated care had better outcomes for children and young people with eating disorders compared to the standard care. Integrated care reduced the hospital admissions to psychiatric wards. However, the study’s quality was weak as it evaluated an integrated care model from over 20 years ago and from a single location. For this reason, these findings should be interpreted with caution.